KAJIAN LITERATUR: SUNAT PEREMPUAN DITINJAU DARI ASPEK UMUM DAN KESEHATAN - Fitri Kurniati; Fitri Fujiana; Uray Fretty Hayati (STIKes Al-Insyirah Pekanbaru, 2022)
Background: Female genital mutilation raises pros and cons among the community because of its impact. There are still many parents who perform genital mutilation on their daughters. In addition, some parents choose not to circumcise their daughters. Objective: To analyze the general impact and health impact of female genital mutilation. Methods: a literature review by searching related articles through the Google Scholar database, Researchget and Science Direct. The keywords used in Indonesian are